Measuring the management of corporate social responsibility from the state in the labor field and promotion of employment - Taquía Gutiérrez, Rossana (2018)
This article raises the possibility of measuring the management of corporate social responsibility from the workplace and employment promotion. Raises a question: How should corporate social responsibility be measured? Today, organizations, whether public or private, measure all the activities they carry out with results or product indicators, only in this way they can establish progress in meeting the goals that have been set, which is established urgently today, even more so when each more time it is required that their Sustainability Reports have more accountability, to their stakeholders, when today in the case of corruption, compliance becomes necessary to establish or improve at all levels, when managing under international standards, (example: ISOS ) of anticorruption, of environmental care, quality, security, etc., they seek to work by measuring the management of the organization and taking action against it.The relevance and innovation of the article is to notice its application in the country from the public sphere, sustains the importance of socially responsible management in the field of work and promotion of employment